Situs Inversus Totalis in a Five-month-old Male Child Presenting with Cough: Diagnostic Clinical Images - Sayali Sanjay Borse; Renu B Rathi (Journal of Clinical and Diagnostic Research, 2024)
A five-month-old male child was brought by his parents to the Paediatric Outpatient Department, MGACH and RC with complaints of a persistent cough for a week. The cough was non productive and associated with mild fever. There was no significant past history of Inpatient Department admissions or any surgical procedures. The infant was born to a primiparous mother at full term via normal delivery. There was no significant family history of diabetes mellitus, hypertension, or known cases of any serious illness in close relatives.